(untitled) (Nuntius Antiquus, 2013)
The purpose of this work is based on the following issues: how the religious aspect is focused on biographical works and what constitutes its function; how religious discourse interferes with conception of the genre of biographical and literary prose from the perspective of Lucian of Samosata. For that we will use as a benchmark for our analysis some conceptions about the religious phenomenon in works with biographical tone of Isocrates, Plato and Xenophon, in order to check how Lucian resumes and refigure issues there proposed. In a kind of biographical account and in epistolary form, Lucian somehow promotes a mimesis (here in the sense of a critical refiguring) of reports of Bios, in which he enacts a moral action figure, syncretizes or juxtaposes philosophical adhesion and religious belief. In the biographical works of Lucian: The passing of Peregrinus, Alexander the false prophet, Demonax and somehow Nigrinus, ‘conversion to a current philosophical’ concerns a pathos in the discourse, which is staged so explicitly dramatized and therefore undergo a treatment critical. Thus, we treat this work in order to delineate the constitution of pathos of biographical discourse and status of a distinctive literary biographical prose linked to religious and philosophical questions.